PENGEMBANGAN PERANGKAT PEMBELAJARAN KOMPETENSI TEKS ANEKDOT BERTEMAKAN KONFLIK SOSIAL DI KALANGAN REMAJA - M. Miftah; Kartika Candra Dewi (Kwangsan: Jurnal Teknologi Pendidikan, 2016)
Learning device has an important role in the learning process for teachers as well as learners, but there are some teachers haven’t optimized the learning device. The purposes of its study are : to determine the needs of the learning device according to teachers and learners; to describe the characteristics of a learning tool; to develop a prototype device which is suitable with the learners need, and to measure the effectiveness of the learning device. The research method used is a research and development method. The results of the study include: the needs of the learning device anecdotal text competence; the characteristics of the learning device anecdotal text competence; a feasibility study based on each device (syllabus, lesson plans, teaching materials and worksheets); the effectiveness of the learning device in producing anecdotes text is shown based on this information; learning without using the learning device obtaining the value of 25 (62.5%), learning with an effective value category and increased by 38 (94.5%) categorized as very effective when learning to use the device. AbstrakPerangkat pembelajaran memiliki peran penting dalam proses pembelajaran namun masih banyak guru belummengoptimalkannya. Tujuan penelitian ini adalah untuk: mengetahui kebutuhan perangkat pembelajaran menurut guru dan peserta didik; menjelaskan karakteristik perangkat pembelajaran; mengembangkan prototipa perangkat pembelajaran yang layak untuk peserta didik; dan menguji keefektifan perangkat pembelajaran. Metode penelitian menggunakan penelitian dan pengembangan (reasearch and development). Hasil penelitian berupa: kebutuhan perangkat pembelajaran kompetensi teks anekdot; karakteristik perangkat pembelajaran kompetensi teks anekdot; kelayakan perangkat pembelajaran berdasarkan silabus, RPP materi pembelajaran, dan lembar kerja; keefektifan perangkat pembelajaran memproduksi teks anekdot ditunjukkan berdasarkan pembelajaran tanpa menggunakan perangkat pembelajaran memperoleh nilai 25 (62,5%) dengan kategori nilai efektif dan mengalami kenaikan sebesar 38 (94,5%) dengan kategori sangat efektif di saat pembelajaran menggunakan perangkat.